Freeze-cast Porous Chitosan Conduit for Peripheral Nerve Repair - Yin, Kaiyang (MRS Adv, 2018)
A novel freeze-cast porous chitosan conduit for peripheral nerve repair with highly-aligned, double layered porosity, which provides the ideal mechanical and chemical properties was designed, manufactured, and assessed in vivo. Efficacies of the conduit and the control inverted nerve autograft were evaluated in bridging 10-mm Lewis rat sciatic nerve gap at 12 weeks post-implantation. Biocompatibility and regenerative efficacy of the porous chitosan conduit were evaluated through the histomorphometric analysis of longitudinal and transverse sections. The porous chitosan conduit was found to have promising regenerative characteristics, promoting the desired neovascularization, and axonal ingrowth and alignment through a combination of structural, mechanical and chemical cues.